Influence of Cord Parameters on the Load Characteristics of Airbags - Yu-Ru Li; Shou-Ne Xiao; Jun-Ke Xie; Tao Zhu; Bing Yang; Guang-Wu Yang; Shi-De Xiao (Shock and Vibration)
To accurately characterize the large deformation and nonlinear characteristics of airbags, the influence of cord parameters on vertical force characteristics was studied, and a finite-element simulation model of airbags based on gas-solid coupling was established. First, uniaxial tension and compression experiments with airbag under different initial pressures were carried out to analyse the effects of the initial pressure and working height on the mechanical properties of the airbag. Second, the validity of the model was verified by the test data of the vertical force and cavity pressure of the airbag. Finally, based on the gas-solid coupling model proposed, the influence of the cord parameters on the vertical force characteristics was studied. The results show that the vertical force characteristics of an airbag are different between compression and tension and the nonlinear characteristic of the airbag becomes more obvious with the increase in the displacement in compression. After comparing the effects of cord parameters on the vertical force of the airbag, we can conclude that the number of cord layers has the most significant effect on the vertical force, followed by the cord diameter, while other cord parameters have a general effect. Under the same compression and tension displacements (d = ±80 mm), the effective area of 1 cord layer is 2.56 times as much as the effective area of 6 cord layers and the vertical force of the airbag with a cord diameter of 0.25 mm is 7.28 times greater than that of the corresponding vertical force with a cord diameter of 1.0 mm. The airbag with different cord angles shows differences in the working state of compression and tension, especially in compression. The force of the airbag at 90° cord angle gradually exceeds the force at other angles with an increase in displacement. The difference in the load at different working states of compression and tension is useful.